2 Combat use of opioid analgesia and its complications: a retrospective review of data from OP herrick. Issue 3 (18th July 2018) - Lewis, P; Wright, C; Hooper, C
Abstract : Background: On the battlefield, acute pain, particularly secondary to trauma, is a common condition which requires treatment in the pre-hospital, evacuation and hospital settings. The use of morphine to manage pain during combat has been well established since the 19th century. Despite this, there are relatively few papers reviewing analgesia use in a combat environment. This study aims to review the use and complications from morphine and other opioids during Op HERRICK. Methods: A database search of the Joint Theatre Trauma Registry (JTTR) was carried out looking for all incidences of administration of either morphine, fentanyl or naloxone from January 2007 to September 2014. Microsoft Excel was then used to analyse the dataset and perform descriptive statistics on the data retrieved. Results: Opioid analgesia was administered to 5801 casualties. Morphine was administered 6742 times to 3808 patients. Fentanyl was administered 9672 times to 4318 patients. Naloxone was used 18 times on 14 patients, giving a complication rate of 0.24%. Opioid doses prior to naloxone administration range from 0–72 mg of morphine and 0–100 mcg of fentanyl. 4 casualties (2 local civilian and 2 coalition forces) received naloxone despite no recorded opioids being administered. Opium abuse was prevalent amongst the local population in Afghanistan, and this could explain the rationale behind 2 local national casualties receiving naloxone without any documented opioids being given. Conclusion: The use of opioids in a battlefield environment is extremely safe, with very few incidences of complications requiring the use of naloxone. Complication rates are comparable to previously published research. We are unable to comment on the effectiveness of opioids in relieving pain in this study, and further research is needed, particularly following the introduction of oral transmucosal fentanyl citrate (OTFC) and the availability of non-opioid analgesia.